Fish oil and probiotics supplementation through milk chocolate improves spatial learning and memory in male Wistar rats - Faccinetto-Beltrán, Paulinna; Aguirre-López, Luis Octavio; Bañuelos-Pineda, Jacinto; Reza-Zaldívar, Edwin E.; Santacruz, Arlette; Hernández-Brenes, Carmen; Pérez-Carrillo, Esther; Jacobo-Velázquez, Daniel A. (Frontiers in Nutrition, 2022)
Background Cognition and brain function is critical through childhood and should be improved with balanced diets. Incorporating bioactive ingredients such as omega-3 polyunsaturated fatty acids (ω3 PUFAs) and probiotics into food formulations could be used as an approach to improve cognitive function. This study evaluated the effects on cognitive capacity of complementing rodent diets with chocolate, by itself and in combination with ω3 PUFAs from fish oil and probiotics. Methods Spatial learning and memory in the rats were determined by the Barnes maze test in short- and long-term memory. Samples from the cecum were obtained to assess microbial counts (Lactobacillus, Bifidobacterium, Enterobacteriaceae, and total bacteria), and brains were recovered to analyze the neural morphology of the tissues. Also, glucose, brain weights, and epididymal tissue were analyzed. Results The combination of chocolate with fish oil and probiotics improved the memory of rats compared to the result of each bioactive compound when evaluated separately. Treatments did not affect sugar level, epididymal adipose tissue, or brain weight. On the other hand, consuming probiotics alone or in combination with chocolate decreased Enterobacteria counts, while Lactobacillus and Bifidobacteria counts were not affected. Neural morphological analysis showed that combining chocolate with probiotics and ω3 PUFAs increased the number of neurons in the hippocampal CA1 and CA3 regions. Conclusion Chocolate added with probiotics and ω3 PUFAs improved spatial memory and learning in the studied model.